Contextual Teaching Learning: Improve Critical Thinking Skills in Ship Stability - Ari Sriantini; Mochamad Cholik (International Journal of Scientific Multidisciplinary Research, 2024)
This research aims to improve students' critical thinking skills through a contextual teaching-learning model in a ship stability course. This qualitative study employs a case study approach to deeply understand the application of contextual teaching in ship stability courses. The data collection method uses written tests and interviews. The subjects are all 38 third-semester Ship Operation Engineering Technology Study Program students in the 2023/2024 academic year. Tests were conducted twice: pre-test and post-test. The average pre-test score for critical thinking was 52.38, and the post-test average was 82.45, categorized as very good. The analysis concluded that students' scores were shallow before contextual learning but improved significantly to an excellent category after the application